Intervening in Alcoholism: How to resolve an ethical dilemma - Calam, Betty (1991)
A case of alcoholism, often encountered in family practice, can illustrate some of the ethical issues that are inherent in the practice of medicine. The concepts of autonomy, paternalism, and beneficence are explored within the context of this clinical example. The nature of alcoholism, options for treatment, the unique circumstances of the patient and family involved, and the complexities of the physician-patient relationship enter into the discussion.